Primary gastrointestinal Kaposi's Sarcoma in a patient with Human immunodeficiency virus (2018)
Gastrointestinal bleeding in HIV patients secondary to coinfection by HHV8 and development of Kaposi’s sarcoma (KS) is a rare complication even if no skin lesions are detected on physical examination. This article indicates which patients might develop this type of clinical sign and also tries to recall that absence of skin lesions never rules out the presence of KS, especially if gastrointestinal involvement is documented. Gastrointestinal bleeding in terms of hematemesis has rarely been reported in the literature. We review some important clinical findings, diagnosis, and treatment approach. We present the case of an HIV patient who presented to the emergency department with hematemesis and gastrointestinal signs of KS on upper gastrointestinal endoscopy without any dermatological involvement.